Tărnovgrad Viewed by the Others: the Case of Niketas Choniates - Marinow, Kirił (Studia Ceranea, 2021)
The text is devoted to the analysis of the portrayal of Tărnovo, the new capital of the restored near the end of the twelfth century Bulgarian state, in the historical work and speeches by Niketas Choniates, a Byzantine historian, official and rhetorician from the latter half of the twelfth and early thirteenth centuries. As a direct witness of the contemporary Byzantine-Bulgarian relations, a high ranking court dignitary throughout most of the discussed period, and the author of the most important sources shedding light on the restitution of Bulgaria, he left a legacy of extraordinary importance, one which has shaped views of the subsequent generations of Byzantine historians. While examining Tărnovo’s role shows it did not occupy a particularly significant place in the historian’s narrative, and the remarks concerning it appear as if in passing, he nonetheless was fully conscious of the city’s significance not only for the Bulgarians themselves, but also in the context of the prospective expansion of the Empire in the direction of its northern neighbours. It is therefore no accident that in his brief characterisation the city the author focused on the description of the defensive qualities of Tărnovo. Paradoxically, his arguments on this subject may play an important role in the present ongoing discussion among the archaeologists exploring the former capital on the subject of chronology and size of the fortifications surrounding the two most important hills on which the city developed, namely Tsarevets and Trapezitsa.